Successful product development: a comparison of practices in the Malaysian and UK industries / Dr. Marzuki Ibrahim - Ibrahim, Dr. Marzuki (2002)
This paper describes an investigation into the new product development (NPD) practices of successful Small Medium Enterprises (SME) manufacturers and consultancies in Malaysia and the UK. The aim was to identify best practice in the NPD process for comparison across the two countries. The investigation focused on the factors: customers and marketing, product design and development, technical and management. A literature search derived a "model of existing best practice" found in larger companies. A comparison of the results indicated how best practice might be redefined in order to make them applicable to the Malaysian SME context.